2010
DOI: 10.1002/cncr.24897
|View full text |Cite
|
Sign up to set email alerts
|

Pulmonary dysfunction in survivors of childhood hematologic malignancies after allogeneic hematopoietic stem cell transplantation

Abstract: BACKGROUND:The number of long-term survivors of allogeneic hematopoietic stem cell transplantation (allo-HSCT) is increasing; however, few studies have addressed their long-term pulmonary function. METHODS: The authors examined 660 baseline and follow-up pulmonary function tests in 89 long-term survivors of pediatric hematologic malignancies and allo-HSCT. RESULTS: At least 1 abnormal lung parameter was seen in 40.4% of baseline tests and developed in 64% of post-allo-HSCT tests (median follow-up: 8.9 years). … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

6
56
2
1

Year Published

2011
2011
2023
2023

Publication Types

Select...
9
1

Relationship

2
8

Authors

Journals

citations
Cited by 52 publications
(65 citation statements)
references
References 25 publications
6
56
2
1
Order By: Relevance
“…We confirmed that patients with refractory disease had significantly worse PFTs post-aHSCT compared with patients in complete remission or patients with nonmalignant disease. 6,11,12 We did not find any significant correlation between age, CMV status, or earlier pulmonary-toxic chemotherapy and pre/post-aHSCT lung function parameters, morbidity, or mortality. In a study of 90 pediatric aHSCT recipients, Lee et al 13 reported on the respiratory failure and mortality 5 of 6 patients with suspected or confirmed CMV pneumonia.…”
Section: Discussionmentioning
confidence: 51%
“…We confirmed that patients with refractory disease had significantly worse PFTs post-aHSCT compared with patients in complete remission or patients with nonmalignant disease. 6,11,12 We did not find any significant correlation between age, CMV status, or earlier pulmonary-toxic chemotherapy and pre/post-aHSCT lung function parameters, morbidity, or mortality. In a study of 90 pediatric aHSCT recipients, Lee et al 13 reported on the respiratory failure and mortality 5 of 6 patients with suspected or confirmed CMV pneumonia.…”
Section: Discussionmentioning
confidence: 51%
“…The natural history of pulmonary function impairment has not been well recognised. Recently, Inaba et al 9 investigated the pattern of pulmonary dysfunction over time in 89 CCSs. They showed that pulmonary function progressively declined.…”
Section: Discussionmentioning
confidence: 99%
“…43,45,46,48,49,52,55,99 The most commonly reported fi nding is a restrictive ventilatory defi cit, sometimes associated with a decrease in D lco . 40,42,43,45,[47][48][49]50,51,[53][54][55]58 In a cohort of survivors of childhood hematologic malignancies after allogeneic HSCT (n 5 89), Inaba et al 62 showed progressive worsening of pulmonary function measured with forced midexpiratory fl ow (25%-75%), residual volume, TLC, and D lco during a median follow-up of 8.9 years.…”
Section: Other Risk-based Factors For Lung Damagementioning
confidence: 99%